2018
DOI: 10.20319/pijss.2018.41.7786
|View full text |Cite
|
Sign up to set email alerts
|

The Economic and Social Benefits of Air Transportation to Tourism in Nigeria

Abstract: The increasing accessibility of air flight has significantly widened air industry's role in our contemporary social settings. As aircraft is no more an expensive valuable but rather a necessity. The aviation sector has not only support wealth generation in the advanced nations, but has also bought humongous impacts to advanced industrialization by tapping their endowment for business and tourism .The paper has kept us informed on about economic and social impact of aviation industry to tourism and its immensel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Most of the empirical inquiries (Arize, 1996) focused attention on industrial and advanced (particularly, European, Asian, American) economies. In addition, available extant studies based exclusively on African/Nigerian data (Abdullahi & Jibir, 2018;Doki & Tyokohol, 2019;Duru & Ehidiamhen, 2018;Hesse, 2008;Hodey et al, 2015;Huseyin & Shuaibu, 2020;Johnson, 2016;Lugeiyamu, 2016;Matezo et al, 2021;Nwosa et al, 2019;Odularu, 2009;Oyelami & Alege 2018;Owan et al, 2020;Vakataki'Ofa et al, 2016;Yuni et al, 2020) that have examined the nature of the relationship between export diversification and economic growth have focused mainly on investigating the growth impacts of overall export diversification which by its nature have been far from being definitive on comparative analysis of the effects of export diversification at intensive and extensive margins on growth. Specifically, no known study has been reported exclusively for Nigeria.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Most of the empirical inquiries (Arize, 1996) focused attention on industrial and advanced (particularly, European, Asian, American) economies. In addition, available extant studies based exclusively on African/Nigerian data (Abdullahi & Jibir, 2018;Doki & Tyokohol, 2019;Duru & Ehidiamhen, 2018;Hesse, 2008;Hodey et al, 2015;Huseyin & Shuaibu, 2020;Johnson, 2016;Lugeiyamu, 2016;Matezo et al, 2021;Nwosa et al, 2019;Odularu, 2009;Oyelami & Alege 2018;Owan et al, 2020;Vakataki'Ofa et al, 2016;Yuni et al, 2020) that have examined the nature of the relationship between export diversification and economic growth have focused mainly on investigating the growth impacts of overall export diversification which by its nature have been far from being definitive on comparative analysis of the effects of export diversification at intensive and extensive margins on growth. Specifically, no known study has been reported exclusively for Nigeria.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…The authors further emphasized that privacy risk does have a predominantly negative influence on tourist experience. Furthermore, Tourism is a growing industry that provides economic and social benefits (Abdullahi et al, 2018) STD managers should take the privacy concern problems associated with the mobile devices to use seriously and must be blended into their ethical perspective when marketing a tourist destination. Nevertheless, the STD designed to enrich the tourist experiences and to improve the competitiveness of each destination.…”
Section: Smart Devices Concerns In Smart Tourism Destinationmentioning
confidence: 99%
“…Literature suggests that African countries should advance their airports to attract more tourists. Therefore, the role of airport departure non-processing domain in tourism performance should not be treated as piecemeal but as a factor influencing tourists' satisfaction [15]. [16] recommended more research on the relationship because of the global competition in the tourism industry.…”
Section: Introductionmentioning
confidence: 99%